DEVELOPMENT OF CREATIVE COMPETENCES OF FUTURE PRESCHOOL EDUCATIONAL TEACHERS (Web of Teachers: Inderscience Research, 2025)
This article examines the issues of developing creative competencies of preschool students. Several functions, approaches, and ways of forming them are presented to improve the pedagogical activity of the future educator and develop a creative environment in the pedagogical process.